Cardiac imaging in cardiovascular complications due to COVID-19 - Galuh, Lukitasari Ayu; Sargowo, Djanggan; Satrijo, Budi; Handari, Saskia Dyah; Rahimah, Anna Fuji (Heart Science Journal, 2024)
Cardiovascular complications are a common manifestation of acute phase and chronic phase of coronavirus disease 2019 (COVID-19) infection. Complications include cardiomyopathy, myocardial infarction, arrhythmias, heart failure, and deep venous thrombosis. Imaging is widely used in patients with suspected myocardial injury or myocarditis. Because of its availability and portability, transthoracic echocardiography (TTE) is used as the initial imaging modality in patients with suspected COVID-19 myocarditis. Echocardiographic studies performed on patients with suspected or confirmed COVID-19 should be as focused as necessary to obtain diagnostic views but should also be comprehensive enough to avoid the need to return for additional images. Following COVID-19 infection, a variety of persistent respiratory, neurological, cardiovascular, and other symptoms can persist for weeks, months, or even years. A cardiac examination and any resulting abnormalities in the structure and function of the heart may occasionally last for several months following a COVID-19 diagnosis. This is referred to as long Â COVID syndrome. Cardiac magnetic resonance (CMR) imaging has often been used clinically to complement echocardiography, particularly tissue characterization imaging which demonstrated subclinical myocardial edema with or without fibrosis in patients recovered from illness.